Organic Compounds: Contents and Their Role in Improving Seed Germination and Protocorm Development in Orchids. (11th June 2020) - Utami, Edy Setiti Wida; Hariyanto, Sucipto
Abstract : In nature, orchid seed germination is obligatory following infection by mycorrhizal fungi, which supplies the developing embryo with water, carbohydrates, vitamins, and minerals, causing the seeds to germinate relatively slowly and at a low germination rate. The nonsymbiotic germination of orchid seeds found in 1922 is applicable to in vitro propagation. The success of seed germination in vitro is influenced by supplementation with organic compounds. Here, we review the scientific literature in terms of the contents and role of organic supplements in promoting seed germination, protocorm development, and seedling growth in orchids. We systematically collected information from scientific literature databases including Scopus, Google Scholar, and ProQuest, as well as published books and conference proceedings. Various organic compounds, i.e., coconut water (CW), peptone (P), banana homogenate (BH), potato homogenate (PH), chitosan (CHT), tomato juice (TJ), and yeast extract (YE), can promote seed germination and growth and development of various orchids. They also stimulate seedling development, formation of protocorm-like bodies (PLBs), plantlet growth, and multiple shoot formation. The addition of organic compounds to culture media, individually or in combination, accelerates seed germination and seedling development. Different types and concentrations of organic nutrients are needed for the success of in vitro cultures, depending on the species and genotype.